Keberkesanan Pengurusan Perubahan di Sekolah - Azman, Abbas (1998)
Effective management of educational change is an important element in ensuring our sustainable competitive advantage. Realizing this, the research was carried out to identify the external and internal factors that influence changes in schools. Based on extensive review of literature, the researcher had identified the three change management processes practiced in effective school. These processes were defreezing, moving and refreezing. A case study method was utilized, triangulated data were gathered through the use of participant observation and interviews with two group of respondents, that is, the principals and teachers of three selected schools. For the purpose of interviews, two set of semi-structured guide questions were prepared. The result of the analysis indicated that respondents had a fairly good understanding of educational change. Principals with an in-depth understanding of the importance of educational change succeeded in managing change effectively. The external factors perceived as influencing the change in school were identified as politics, social, economics and technological development. The internal factors that influences the change management in school were identified as schools leadership which includes the knowledge and experience of the principal. Teachers’ past experiences and workload influence teachers attitudes towards change. The analysis also revealed that effective change managers practiced the three change management processes effectively. Sample schools were found to implement the process of defreezing by dissemination of information to their teachers by various approaches. The process of moving was executed by having talks and in-house training while refreezing by having a continuous staff develoment programmes and teachers recognitions. The study also showed that effective change management would have effects on the organizational cultures and the school norms. It was also found that proper recognition for teachers would increase their self esteem and thus their receptivity towards educational change. As a summary, the study verified that effective change management in schools depends on the competencies of the schools management to execute the three prosesses of managing change effectively.